Self-reseeding annual legumes for cover cropping in rainfed managed olive orchards - Rodrigues, M. Ângelo; Ferreira, Isabel Q.; Freitas, Sara L.; Pires, Jaime M.; Arrobas, Margarida P. (Spanish Journal of Agricultural Research, 2015)
Given the environmental impact of nitrogen (N)-fertilizer manufacture and use, the sustainable management of agro-systems should be sought by growing N-fixing legumes. In this work, eleven self-reseeding annual legumes were grown in pure stands as mulching cover crops in a rainfed olive orchard managed without grazing animals. Dry matter yield, N content in above-ground biomass, groundcover percentage and persistence of the sown species were assessed during four growing seasons. All covers provided enough soil protection over the year, with living plants during the autumn/winter period and a mulch of dead residues during the summer. The legumes overcame a false break observed in the third year recovering the dominance of the covers in the fourth growing season. This means that the seed bank established in previous seasons ensured the persistence of the sown legume even when a gap in seed production occurred. The early-maturing cultivars produced less biomass and fixed less N (approx. 50 kg N/ha/yr present in the above-ground biomass) than the late-maturing ones, but would compete less for water since the growing cycle finished earlier in the spring. They seem best suited to being grown in dry farmed olive orchards with low N demand in drought prone regions.